Effectiveness of Basil Leaf Nanoparticle Supplementation on Stress Levels and Breast Milk Adequacy in Postpartum - Choerunnisa, Choerunnisa; Pujiastuti, Rr. Sri Endang; Kusmiyati, Yuni (Amalee: Indonesian Journal of Community Research and Engagement, 2024)
The prevalence of stress events in postpartum increases every year, the result can inhibit the adequacy of breastfeeding in postpartum. To overcome the problem of stress and adequacy of breast milk, basil leaves are an alternative plant that can function as a lactagogue and prevent stress complications is the supplementation of basil leaf nanoparticles. increase the absorption of drugs by the body. This study aims to determine the effectiveness of basil leaf nanoparticles on stress levels and adequacy of breast milk in post-partum. The research method uses quantitative research with quasi-experimental methods with probability sampling, design pre and post-test with control group. The results showed that the stress level in the intervention group was proven to reduce stress levels with an average of 18.50 before being given treatment and an average of 11.18 after treatment. Administration of basil leaf nanoparticles showed a significant difference in reducing stress levels. In the indicator of adequacy of breastfeeding in the form of baby's weight (p<0.005) frequency of bowel movements (p<0.005) frequency of bowel movements (p<0.005) and frequency of breastfeeding (0.369<0.005) means that there are differences in baby's weight, frequency of bowel movements, frequency of urination, and the frequency of breastfeeding in the intervention group and the control group